Beyond Brinkmanship: The Implication of South China Sea Conflicts on China’s Soft Power in Southeast Asia - Randy Wirasta Nandyatama (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2019)
While contemporary scholarly literatures on South China Sea conflicts have been dominated by hard power calculations, some other aspects remain under-researched. Rather underplayed in the existing literature is the question on the political implication of the conflicts on China’s soft power in the region. In responding to this issue, this article tries to carefully investigate the nature of the China’s soft power and the linkage between the increasing Chinese assertive measures in the South China Sea and the foundation of China’s soft power in the region. Through some cases of China’s skirmishes with Southeast Asian countries on the South China Sea between 2009 and 2012, this article argues that Beijing’s increasing hard power measures have induced growing threat perceptions in the region. This very context not only signals a distinct dissonance of Beijing’s image in Southeast Asia but also creates surging discontents and rejections to China’s role and political position in the region. Ultimately, China’s perceived inappropriate hard power measures affect its soft power, particularly in eroding the reputation of being a benign political entity as its source of soft power in Southeast Asia.